Redirecting public oral health fluoride varnish intervention to low socio-economic status children in Alberta - Huber, Cynthia (Can J Public Health, 2017)
SETTING: Dental decay is most prevalent among low socio-economic status (SES) groups where cost limits access to dental care. To address inequities in oral health outcomes, Alberta Health Services (AHS) Oral Health Action Plan encompasses a population health approach that redirects fluoride varnish (FV) applications to low SES children. Using low SES measures to establish the eligibility criteria is fundamental to the delivery of FV applications to the target population. INTERVENTION: A series of four FV applications over two years is directed to children age 12–35 months and two applications per year to children in Kindergarten and grades 1 and 2, using low SES measures for eligibility criteria. The provincial objective for children receiving the first FV application is 10%–20% of the population age. Additional objectives are set for rates of subsequent FV applications for each population group. OUTCOMES: From 2015 to 2016, the rate of first FV applications for eligible target populations is below the provincial objective for children age 12–35 months (5%) and within the objective for children in Kindergarten and grades 1 and 2 (16%). Rates of subsequent FV applications in the school setting are being met. IMPLICATIONS: Encompassing a population health approach to deliver standardized fluoride varnish applications to low SES children better targets inequities in oral health outcomes in Alberta. Challenges of redirecting the FV intervention include creating the eligibility criteria and engaging the target population, particularly for the preschool population. Achieving population objectives are challenged by unequal distribution of resources across the province.